Analisis Pengaruh Nilai Pelanggan, Kualitas Pelayanan Dan Kedekatan Emosional Terhadap Loyalitas Pelanggan Di PT. FIFGROUP Kios Tandem Mijen Semarang - Silvia Rachmawati; Mulyo Budi Setiawan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Customers who are loyal to the company will give top priority in choosing the services they will use. Business needs value creation to customers to be successful. This study aims to analyze the effect of customer value, service quality and emotional closeness on customer loyalty at PT. FIFgroup Mijen Tandem Kios Semarang. The sample in this study was 100 customers. Data collection techniques using questionnaire media. Processing the results of the questionnaire using multiple linear regression analysis assisted by the SPSS program. The results of the study prove that customer value has a positive effect on customer loyalty, emotional closeness has a positive effect on customer loyalty. However, the service quality variable has no effect on customer loyalty. The results of the test for the coefficient of determination show a value (Adjusted R Square) of 0.416, namely 41.6%, the variation in the amount of customer loyalty can be explained by changes that occur in the variables Customer Value, Service Quality and Emotional Closeness. While the remaining 58.4% is influenced by other variables not included in the study. Keywords : Customer Loyalty, Customer Value, Service Quality, Emotional Closeness